ISOLATION, CHARACTERIZATION AND EVALUATION OF ENTOMOPATHOGENIC FUNGI FROM BRAHMINA CORIACEA BEETLES - Sharma, Anupam; Thakur, Desh Raj; Chandla, Virender Kumar (Potato Journal, 2017)
White grub, Brahmina coriacea is one of the most important pests of potato in North western hills of India. In this study, B. coriacea beetles were trapped and investigated for fungal pathogens of this pest. Three fungi were consistently isolated from the infected beetles. Based on partial sequencing of 18S rRNA, ITS1, 5.8S, ITS2 and a partial sequence of 28S rRNA, the isolates were identified as Beauveria bassiana strain CPRI16, Aspergillus flavus strain CPRI18 and Fusarium oxysporum strain CPRI15. Additionally, insecticidal activity of these isolates was determined on B. coriacea grubs, eggs and beetles by testing spore concentration of 1 âˆš 108 spores/ml. The highest mortality of second (92.59%) and third instar grubs (81.85%) was obtained from B. bassiana after 60 days of treatment. All the isolates resulted in 100% mortality of adults. Egg laying and percent hatching of eggs was observed minimum due to A. flavus.